Balloon-Occluded Trans-Arterial Chemo-Embolization Technique with Repeated Alternate Infusion of Cisplatin Solution and Sparse Gelatin Slurry (RAIB-TACE) for Large Hepatocellular Carcinoma Nodules More than 7 cm in Diameter. (20th January 2020) - Irie, Toshiyuki; Takahashi, Nobuyuki; Kamoshida, Toshiro; Kashimura, Junya; Ariga, Hiroyuki
Abstract : Objective . It is sometimes difficult to obtain complete/partial response of large hepatocellular carcinoma (HCC) nodules by trans-arterial chemoembolization/embolization (TACE/TAE). The aim is retrospective investigation of tumor response of large HCC nodules (>7 cm) treated by the new TACE technique, repeated alternate infusion of cisplatin solution, and sparse gelatin slurry under balloon occlusion (RAIB-TACE). Materials and Methods . A microballoon catheter was placed at a proximal portion of the hepatic artery (subsegmental to the lobar level hepatic artery), and alternate infusion of cisplatin solution and sparse gelatin slurry were repeated under balloon occlusion until stasis of gelatin slurry beyond the catheter was seen. RAIB-TACE of multiple proximal hepatic and extrahepatic collateral arteries were performed to treat hemi-lobe or more of the liver while avoiding infusion into gastric and cystic arteries for 19 large nodules (>7 cm) in 19 patients without portal venous invasion. All patients underwent dynamic CT/MRI 1–3 months after RAIB-TACE, and tumor response of each large nodule was evaluated based on modified RECIST criteria. Results . CR, PR, SD, and PD were achieved in 11, 8, 0, and 0 nodules, respectively. CR and PR were considered as success, and the ratio of success was 100%. Major complications were abscess formation in the necrotic nodule ( n  = 1) which was treated by drainage tube placement, and subsegmental level liver infarction ( n  = 1) which recovered uneventfully. Conclusion . New TACE technique, RAIB-TACE, was useful to achieve successful response of large HCC nodules.